Seroprevalence of anti HCV antibodies among blood donors in Kathmandu valley, Nepal - Karki, S; Ghimire, P; Tiwari, BR; Rajkarnikar, M (Kathmandu University Medical Journal, 2009)
Aims and objectives: To study the seroprevalence of anti HCV antibodies among Nepalese blood donors in relation to their age, sex, type of donation and times of donation. Materials and methods: Descriptive cross-sectional study conducted in Nepal Red Cross Society (NRCS), Central Blood Transfusion Service (CBTS), Kathmandu, from December 1, 2006 to September 1, 2007. A total of 33,255 blood donors were screened for anti HCV antibodies by ELISA. Donor's information was collected from blood donor's record form and statistical analysis was done using the software ‘SPSS 11.5' and ‘Winpepi ver. 3.8'. Result: The seroprevalence of anti HCV antibodies in blood donors was 0.66% (95% CI= 0.58-0.76). Higher seroprevalence was observed in male donors (0.7%, 95% CI= 0.6-0.8) than in female donors (0.4%, 95% CI= 0.2-0.6) (P < 0.05). The seroprevalence was highest (0.82%) in the age group of 21-30 years and there was significantly decreasing trends in seroprevalence with increasing age (P < 0.05). The highest seroprevalence among the male donors (0.88%) was also observed in the age group of 21-30 years (P < 0.001). Among female donors the seroprevalence (0.47 %) was highest in age group 41-50 years (P > 0.05). The seroprevalence of anti HCV was significantly higher in volunteer donors (0.7%) than in replacement donors (0.4%) (P < 0.05). Similar seroprevalence of anti HCV was observed in first time (0.65%) and repeat blood donors (0.67%) (P > 0.05). Conclusion: The seroprevalence of anti HCV antibodies among blood donors in this study was similar to the seroprevalence reported for general population by other studies. Similar seroprevalence in first time and repeat blood donors as well as higher seroprevalence in volunteer donors than in replacement donors are the potential threats to safe blood supply, which urges the need of more effective donor education and counselling of blood donors. Key words: . doi: 10.3126/kumj.v6i4.1741 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 491-496